RESENHA : ECONOMIA TERRITORIAL: TEORIA E INDICADORES - Christ, Gabriela Daiana (Informe GEPEC, 2023)
Esta resenha versa sobre a obra intitulada “Economia territorial: teoria e indicadores”. Trata-se de um manuscrito publicado no idioma português, organizado em 160 páginas, seis capítulos e cujo público-alvo destina-se a comunidade acadêmica. É uma obra completa onde a teoria é praticada no empirismo da economia territorial por meio de indicadores, o que não esgota o assunto sobre o tema, mas possibilita discussões inovadoras sob a perspectiva da análise territorial. A obra contribui para a teoria e métodos da análise territorial a partir de temas fundamentais para o desenvolvimento territorial, como a distribuição de riqueza, justiça social, mudanças de mentalidade e com sentimento de pertencimento local, com uma governança territorial de mentalidade inovadora, visionária, proativa e empreendedora. É uma obra didática que deve ser lida por todos aqueles que se interessam pelo desenvolvimento territorial e pela compreensão das dinâmicas econômicas em diferentes contextos territoriais. Abstract: This work review is about the book entitled “Territorial economy: theory and indicators”. This is a manuscript published in Portuguese, organized into 160 pages, six chapters, and whose target audience is the academic community. It is a complete work where the theory is practiced in the empiricism of the territorial economy through indicators, which does not exhaust the subject. Still, it enables innovative discussions from the perspective of territorial analysis. The book contributes to the theory and methods of territorial analysis based on fundamental themes for territorial development, such as the distribution of wealth, social justice, changes in mentality and a sense of local belonging, and territorial governance with innovative, visionary, proactive, and enterprising. It is a didactic work that should be read by all interested in territorial development and understanding the economic dynamics in different territorial contexts. Abstract: This work review is about the book entitled “Territorial economy: theory and indicators”. This is a manuscript published in Portuguese, organized into 160 pages, six chapters, and whose target audience is the academic community. It is a complete work where the theory is practiced in the empiricism of the territorial economy through indicators, which does not exhaust the subject. Still, it enables innovative discussions from the perspective of territorial analysis. The book contributes to the theory and methods of territorial analysis based on fundamental themes for territorial development, such as the distribution of wealth, social justice, changes in mentality and a sense of local belonging, and territorial governance with innovative, visionary, proactive, and enterprising. It is a didactic work that should be read by all interested in territorial development and understanding the economic dynamics in different territorial contexts.